2016
DOI: 10.1007/s13224-016-0938-3
|View full text |Cite
|
Sign up to set email alerts
|

Oligoamnios and Perinatal Outcome

Abstract: Oligoamnios has a significant correlation with adverse perinatal outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 15 publications
3
9
0
Order By: Relevance
“…In present study, low birth weight (LBW) was found in 18 (51.43%) cases in group 1 and 12 (18.46%) cases in group 2 and this difference was found to be statistically significant (p=0.001); which is comparable to study by panda et al 9 Showing LBW in 32 % in group 1 and 12 % in group 2 women, indicating oligohydramnios had an association with fetal growth restriction.…”
Section: Discussionsupporting
confidence: 84%
“…In present study, low birth weight (LBW) was found in 18 (51.43%) cases in group 1 and 12 (18.46%) cases in group 2 and this difference was found to be statistically significant (p=0.001); which is comparable to study by panda et al 9 Showing LBW in 32 % in group 1 and 12 % in group 2 women, indicating oligohydramnios had an association with fetal growth restriction.…”
Section: Discussionsupporting
confidence: 84%
“…Similar findings were found in other studies for oligohydramnios mothers. [7][8][9] However, many studies had lower rates of caesarean section. [10][11][12] Our study had a higher number of elective caesarean section, which may be the reason for this conflicting finding.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 In addition, majority of the study have concluded that oligohydramnios and polyhydramnios is associated with increased perinatal complications. [6][7][8][9]11,13 All these factors have lead to a negative trend of increased caesarean section rates. Conducting a randomized control trial on the optimal delivery route for oligohydramnios or polyhydramnios conditions is the best solution, but has ethical issues.…”
Section: Discussionmentioning
confidence: 99%
“…The mean gestational age in the present study 36.7 +/-4.1 weeks. Studies by Jun Zhang et al [3] , Everett et al [4] , Casey B et al [5] and Sandhyasri Panda et al [6] found that the mean gestational age were 38.1 +/-3.3 weeks, 37.5 +/-2 weeks, 34.3 +/-2.1 weeks and was 36.3 +/-2 weeks respectively. These findings indicate that the problem of oligohydramnios was more common in later part of pregnancy.…”
Section: Discussionmentioning
confidence: 99%